Development of methods for identification of informationcontrolling signals of unmanned aircraft complex operator - Yudin, Oleksandr; Ziubina, Ruslana; Buchyk, Serhii; Matviichuk-Yudina, Olena; Suprun, Olha; Ivannikova, Viktoriia (Eastern-European Journal of Enterprise Technologies, 2020)
Methods for verifying and identifying the operator by the features of the formation of biometric features of a speech signal in control systems of unmanned aerial systems are proposed. A method has been developed for the effective width of the spectrum of a speech signal, which allows identification and verification of the operator of an unmanned aerial vehicle based on an analysis of the informative components of voice prints under conditions of a high level of interference of various origins. A method has been developed for the highest informational weight of the fundamental tone, which is based on the use of the most informative components of the spectral representation of the prints of a speech signal. The first method allows to identify the operator of an unmanned aerial vehicle by the informative components of the spectral representation of the fingerprint of a speech signal under conditions of a high level of interference. High indicators, which are achieved by using this method, are obtained due to the uniqueness of the selected feature space, which retain their characteristics even with a fairly high level of interference. The second method provides speaker identification of an unmanned aerial vehicle by a specific space of unique voice features. The frequencies of the fundamental tone and overtones were chosen as the basic features. Such an approach to solving the identification problem provides a high probability of determining the operator with the existing rather high level of interference and reduces the processing time of information in comparison with the effective spectrum width method. The creation of control methods and models for unmanned aerial systems provides an increase in the level of noise immunity and safety of control systems from interventions by an unauthorized operator. Using operator identification methods allows to create a system for restricting access to the aircraft control process and thereby ensure the continuity of the operation of the information management system for unmanned aerial systems